Astronomy education awareness in Malaysia - Zainuddin, M.Z. (2008)
Astronomy education in Malaysia had evolved since 1700's. However it involved the teaching of determining the qibla direction, praying times, crescent observation and some astrology. In the early 1980's awareness of Malaysian Government on the important of space science education had created the Space studies Division (BAKSA) in the Prime Minister Department and Malaysian remote sensing center (MACRES)under Ministry of Science, Technology and Environment (MOSTE). In the 2003, BAKSA had been changed to National Space Agency (NSA). NSA and Ministry of Education (MOE) had been promoting an awareness in space science education mainly in astronomy. They organized national quiz competitions for primary and secondary schools, astronomy projects, rocket launching technology and others. The Malaysian Government had embarked on the astronaut program where the first Malaysian astronaut onboard the International Space Station (ISS) Dr Sheikh Muszaphar Shukor on 12th October 2007. The successful of this astronaut program had created public awareness of space science especially in astronomy. Malaysia had hosted the International school young astronomer 2007. We will be hosting the COSPAR workshop in June 2008. The higher institutions in Malaysia are beginning to pursue the curriculum of astronomy teaching and getting involved with the heliophysical year 2007 and the International year of Astronomy 2009. This paper will be highlighting the effort done in Malaysia to encourage astronomy education from MOE, NSA, Malaysian Government and the Higher Institutions in Malaysia.